2014
DOI: 10.1111/j.1532-950x.2014.12184.x
|View full text |Cite
|
Sign up to set email alerts
|

In VitroMechanical Testing of Braided Polyurethane Elastic Fiber and Braided Polyester for Equine Laryngoplasty

Abstract: Lycra® prostheses embedded in laryngeal cartilage pulled through the cartilage at lower loads than Ethibond™ prostheses. Lycra® suture loops were stronger than Ethibond™ suture loops. Lycra® had greater displacement than Ethibond™ in all tests as suture loops or when embedded in cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…Distraction distance under cyclic load can be interpreted as a measure of the distance an implant could be expected to loosen when used in vivo. Differences in distraction distance are likely because of the effect of cyclic load increasing the rate of implant pull‐through within cartilage or in rare instances implant failure . In our report, the arytenoid‐ZipFix constructs distracted less and withstood a significantly greater load during subsequent load to failure.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Distraction distance under cyclic load can be interpreted as a measure of the distance an implant could be expected to loosen when used in vivo. Differences in distraction distance are likely because of the effect of cyclic load increasing the rate of implant pull‐through within cartilage or in rare instances implant failure . In our report, the arytenoid‐ZipFix constructs distracted less and withstood a significantly greater load during subsequent load to failure.…”
Section: Discussionmentioning
confidence: 54%
“…Multiple alternative materials have previously been evaluated for use in prosthetic laryngoplasty, including a steel cable and washers, an alternate laryngoplasty system, and a monofilament nylon cranial cruciate ligament repair system; however, these reports have each used a different methodology, making it difficult to compare between studies. We replicated the methodology of previous reports for our study to enable comparisons across studies . Although Kelly et al and Dart et al reported that a double strand of suture has a biomechanical advantage in vivo compared with a single strand, we chose to use a single strand so as to solely compare implant materials in similar formats (single stand).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations